2008
DOI: 10.1128/aem.01387-07
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Flavins by Shewanella Species and Their Role in Extracellular Electron Transfer

Abstract: Fe(III)-respiring bacteria such as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
655
4
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 790 publications
(703 citation statements)
references
References 32 publications
28
655
4
5
Order By: Relevance
“…6). Although flavin adenine mononcleotide (FMN) has been detected in supernatants of different Shewanella species [23], we did not detect it in our experiments, perhaps due to differences in experimental design. Surprisingly, the levels of riboflavins in supernatants of Dflg, Dmsh, DpilM-Q, DmtrC /DomcA were similar to wild type levels (Fig.…”
Section: Role Of Riboflavins In Extracellular Electron Transfer In Picontrasting
confidence: 47%
See 1 more Smart Citation
“…6). Although flavin adenine mononcleotide (FMN) has been detected in supernatants of different Shewanella species [23], we did not detect it in our experiments, perhaps due to differences in experimental design. Surprisingly, the levels of riboflavins in supernatants of Dflg, Dmsh, DpilM-Q, DmtrC /DomcA were similar to wild type levels (Fig.…”
Section: Role Of Riboflavins In Extracellular Electron Transfer In Picontrasting
confidence: 47%
“…Recently, flavins were proposed to be soluble mediators in extracellular electron transfer to Fe(III) oxides and to anodes of MFCs [22,23]. To determine if these mediators contributed to the differences in current output by wild type and mutant strains, we measured flavin levels in culture supernatants at the end of the MFC experiments (210 h).…”
Section: Role Of Riboflavins In Extracellular Electron Transfer In Pimentioning
confidence: 99%
“…As this article went to press, von Canstein et al (45) reported secretion of flavins by multiple planktonic Shewanella cultures and noted a role for these compounds in azo dye decoloration and metal reduction. These results are consistent with our findings using biofilm cultures.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…In addition, it has been proposed that secreted flavins, for example riboflavin (RF) and/or flavin mononucleotide (FMN), are reduced by MR-1 cells and then in their free form function as redox mediators for the Mtr pathway, thus facilitating EET reactions (Fig. 1A) (11,12). In support of this hypothesis, it was reported that the removal of flavin from the supernatants of systems with electrode-bound biofilms resulted in an ∼80% loss in microbial current production (12).…”
mentioning
confidence: 99%